An Analysis of Students’ Vocabulary Mastery at SMP Gajah Mada Medan - Merry Susanty Br Tarigan; Nava Arbina Br Sembiring; Grace Martha Elvriani Purba (PT FORMOSA CENDEKIA GLOBAL, 2024)
Vocabulary is a critical component of learning English; for students, it is the first step toward mastery of the language. To communicate effectively, students must have sufficient vocabulary, as well as the ability to utilize it correctly. As a result, the purpose of this study is to assess students' vocabulary mastery. at Gajah Mada Junior High School, specifically in grade VIII. The research method used is descriptive qualitative. In this study, the author employed vocabulary tests and interviews with students, consisting of two vocabulary tests to gather data. The results of the research indicate that the vocabulary mastery of Gajah Mada Junior High School students is still low. This is evident from the first test, where only 9 students scored above 75, and in the second test, only 2 students achieved a score of 75, with the majority of students scoring below 70